Two worlds of retirement income: A comparative analysis of retirement-income outcomes using the Luxembourg Income Study - Kevin Lomax; Brian Gran (Luxembourg Income Study (LIS), 2003)
This paper examines whether retirement-income systems allow older individuals to enjoy socially acceptable income levels independent of paid work (decommodification) and the family (defamilialization). Little research has investigated the degree to which decommodification and defamilialization levels, whether from public or private sources, vary by age. We employ the Luxembourg Income Study to compare Canada, Finland, France, Germany, Sweden, and the United States. This study applies the Pythagorean Theorem to measure autonomy, then explores whether members experience decommodification and defamilialization levels predicted for their system. Our results show Sweden and Canada provide highest autonomy levels, Finland, France and the United States provide moderate levels, and Germany low levels. We find age polarity: Swedes and Finns who are decommodified and defamilialized tend to be younger than age 70. Individuals who are decommodified and defamilialized through the retirement-income systems of Canada, France, Germany, and the United States, however, tend to be older than age 75. Some experts contend systems have converged, yet retirement-income systems do not produce similar autonomy levels. Outcomes for system members vary by age, suggesting reformers cannot take 'one size fits all' approaches.
Keywords: 330; Rentenpolitik; Einkommen; Einkommensverteilung; Disparitätsmaß; Luxemburg; USA; Finnland; Kanada; Deutschland; Frankreich; Schweden; Rentner